Rendezvous with an Eighth Grader: Insights for Design and Technology Education - Muralidhar, Adithi (Voices of Teachers and Teacher Educators, 2019)
This article presents some insights gained through an interview with a middle school student. The interview reported here focused on this student’s likes and dislikes in connection with school, ideas about science, technology, and society etc. Further, the article outlines the key ideas and themes that emerge from a preliminary analysis of this interview. Though one cannot generalize, the evidence transpiring through this exercise do provide some opportunity to reflect on the way we design activities for children.